The impact of government interventions on health, schooling and family planning in the Philippines - Gonzalez, Eduardo T. (1992)
The substitution and complementarity relationships among child health, child schooling, and number of children in a developing-country context are explored, in order to test the thesis that governmental initiatives in health care, education and family planning can be orchestrated in a manner that would permit a cost-effective implementation of the national goals of reduced population growth and increased human capital buildup. Government policy initiatives and an economic economic framework of household decision-making are linked together, using a reduced-form demand model which incorporates unobservable individual and community effects. An instrumental variables estimation technique is used to resolve the combined problem of unobserved effect and the endogeneity of policy variables. The estimation results suggest that households respond optimally to variations in the price of governmental programs by shifting the allocation of family resources from an assured number of children to less but healthier and better-educated children. A carefully designed policy that combines government programs in a mutually reinforcing way would be much more effective than a one-program instrument in improving household welfare.
Includes bibliographical references (pages 50-53).
Keywords: Domestic economic assistance; Family planning; Public health; Public schools